Traduzir filosofia analítica: fundamentos conceituais para uma abordagem funcionalista - Cordeiro, Lucas de Oliveira (2022)
Currently, there are at least three distinct perspectives on the translation of philosophy in translation studies. The first focuses on the issue of untranslatability (CASSIN, 2018); the second claims that every canonical philosophical text is essentially obscure and unwieldy (RÉE, 2001); the third suggests approaching the philosophical text as one translates literature (VENUTI, 2019). We find all these views, to a greater or lesser extent, problematic, and contrast them with two more remote perspectives (INGARDEN, 1991; JAKOBSON, 2010), which go in the opposite direction: they claim that the philosophical text is distinct from the literary text, for example, because it has a distinct (cognitive) function, and should be translated like the scientific text, which has similar functions. Our own view is that this conception is the most appropriate, especially for translation purposes, as far as a particular philosophical tradition, analytic philosophy, is concerned. Our goal is to ground this understanding of the analytic philosophical text as a technical-scientific text in order to provide a conceptual basis for more appropriate, secure, and effective translation approaches. To this end, we draw on two theoretical and practical frameworks of translation studies: German functionalism (NORD, 2018; REISS; VERMEER, 2014), which claims that the most relevant factors in determining translation strategies are the consideration of the function and the readership of the target text; and also some reflections on the translation of technical-scientific texts (BYRNE, 2012; MONTGOMERY, 2010; SCHUBERT, 2010), which are strongly influenced by functionalist ideas. Finally, a cultural characterization of analytic philosophy (BEANEY, 2017; MARCONDES, 2004; GLOCK, 2008), focusing on factors such as this tradition's relationship with science and the view that many of its practitioners have of language & translation, suggests that analytic texts have an eminently cognitive function, and that the communities in which these texts circulate expect this function to be preserved in translations, which would justify our interpretive hypothesis.